2014
DOI: 10.1016/j.jamda.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Hospice in the Nursing Home: Perspectives of Front Line Nursing Home Staff

Abstract: Objective Use of hospice has been associated with improved outcomes for nursing home residents and attitudes of nursing home staff towards hospice influences hospice referral. The objective of this study is to describe attitudes of certified nursing assistants (CNAs), nurses, and social workers towards hospice care in nursing homes. Design, Setting and Participants We conducted a survey of 1,859 staff from 52 Indiana nursing homes. Measurements Study data include responses to 6 scaled questions and 3 open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Frontline staff consistently have lower levels of knowledge about EOL issues when compared to knowledge about physical and psychological domains of care—and the majority of staff would welcome additional education on palliative and EOL care. 16 A synthesis of our qualitative findings provides potential targets for staff education on best practices for EOL care, including 1) knowledge about the dying process, 2) assessment and management of symptoms, 3) an overview of family dynamics and common affective responses, 4) strategies to facilitate communication between staff, other providers, residents, and families, 5) accurate knowledge about hospice and palliative care, 6) a review of ethical and practical dilemmas, and guidance for what to do in such situations, 7) means to preserve patient dignity, and 8) education on self-care. NH staff cope with a myriad of challenges, including compound losses, being the target of family anger and unwarranted criticism, high levels of stress and burnout, and personal discomfort with providing care to dying patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frontline staff consistently have lower levels of knowledge about EOL issues when compared to knowledge about physical and psychological domains of care—and the majority of staff would welcome additional education on palliative and EOL care. 16 A synthesis of our qualitative findings provides potential targets for staff education on best practices for EOL care, including 1) knowledge about the dying process, 2) assessment and management of symptoms, 3) an overview of family dynamics and common affective responses, 4) strategies to facilitate communication between staff, other providers, residents, and families, 5) accurate knowledge about hospice and palliative care, 6) a review of ethical and practical dilemmas, and guidance for what to do in such situations, 7) means to preserve patient dignity, and 8) education on self-care. NH staff cope with a myriad of challenges, including compound losses, being the target of family anger and unwarranted criticism, high levels of stress and burnout, and personal discomfort with providing care to dying patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unroe et al (2014) quantitatively analyzed NH staff perceptions about hospice and found that the majority viewed hospice as generally positive, but more beneficial for patients and families than for the NH staff themselves. The study also found that staff frequently reported poor communication between NH and hospice staff, which could contribute to poorly coordinated care, 16 and ultimately lower the quality of care for dying patients.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This was part of a larger survey that included questions about interactions with hospice, as well as open-ended prompts 14 designed to measure knowledge, practice and attitudes towards both palliative care and hospice by NH staff at multiple levels. In addition to comparing palliative care knowledge and practices across staff roles, we also examined relationships between facility characteristics and PCS scores.…”
Section: Introductionmentioning
confidence: 99%
“…Unroe et al (2014) conducted a survey of staff from several nursing homes in EEUU about attitudes of nursing home staff towards hospice, and found that more social workers responded favourably to hospice involvement in nursing homes compared to nursing assistants.…”
Section: Discussionmentioning
confidence: 99%